ROAR ED-SANE: A Retrospective Observational Assessment Review of an Emergency Department Sexual Assault Nurse Examiner Program's Adherence to Centers for Disease Control and Prevention Guidelines for Sexually Transmitted Infections. Issue 3 (1st March 2023) - Nelson, Jennifer M.; Woolever, Nathan; Meyer, Lisa; Hall, Scott; Stakston, Jaclyn; Dababneh, Ala; Roush, Kathleen; Van Sistine, Michael; Tempelis, Jennifer; Dierkhising, Ross A.; Lessard, Sarah
Abstract : Review of an emergency department sexual assault nurse examiner program's prescribing and follow-up scheduling adherence to Centers for Disease Control and Prevention guidelines found prescribing adherence in 4 of 7 indications and suboptimal scheduling adherence. Abstract : Background: Sexual assault survivors are at increased risk for sexually transmitted infections. Sexual Assault Nurse Examiner programs guide sexually transmitted infection treatment, monitoring, and follow-up scheduling according to guidelines by the Centers for Disease Control and Prevention (CDC). Reported low rates of provider adherence to CDC treatment guidelines and patient adherence to follow-up necessitate a review of medication prescribing and follow-up scheduling practices, especially at smaller community hospitals in the United States. Methods: A retrospective medical record review was conducted to assess adherence rates to CDC guidelines for prescribing practices, scheduling, and follow-up of sexual assault survivors. We included pediatric and adult patients presenting to the emergency department (ED) and participating in the ED Sexual Assault Nurse Examiner program at a rural, community-based teaching hospital in La Crosse, WI, from January 2018 to December 2021. Descriptive statistics were used to evaluate results. Results: Analysis included 103 patients. Prescribing adherence to CDC guidelines was >80% for all except human immunodeficiency virus (53.4%), trichomoniasis (68.1%), and hepatitis B (69%). Of the 38 patients who had a follow-up scheduled during their ED encounter, 78.9% attended their scheduled follow-up and 94.7% of those appointments were scheduled within the CDC-recommended time frame, leading to an overall adherence of 40%. Conclusions: Adherence rates were high for most prescribing practices, and attendance of scheduled follow-up was higher than expected. Opportunities to improved adherence to CDC guidelines were identified in prescribing for 3 disease states (human immunodeficiency virus, trichomoniasis, and hepatitis B) and in scheduling of follow-up.